Evaluating Medxa SIMRS Implementation Success Using HOT-Fit and Multiple Regression - Muhammad Haykal Alfariz Saputra; Ermatita Ermatita (Asosiasi Doktor Sistem Informasi Indonesia, 2026)
The implementation of Hospital Management Information Systems (HMIS) is essential for improving service quality, strengthening operational efficiency, and supporting evidence-based decision-making in hospitals. Nevertheless, the success of HMIS implementation is shaped not only by technological performance, but also by human and organizational factors. This study aimed to evaluate the implementation success of Medxa SIMRS at Mohammad Hoesin Hospital, Palembang, using the Human–Organization–Technology Fit (HOT-Fit) model. A quantitative cross-sectional survey was conducted among 67 active users of Medxa SIMRS using a structured Likert-scale questionnaire. Data were analyzed using descriptive statistics and multiple linear regression in Python to examine the influence of the Human, Organization, and Technology dimensions on Net Benefit. The descriptive findings showed that all HOT-Fit dimensions were rated in the good to very good categories, indicating generally positive user perceptions of the system. Regression analysis demonstrated that, simultaneously, the Human, Organization, and Technology dimensions significantly explained variation in Net Benefit (p < 0.05). However, in the partial analysis, only the Technology dimension had a statistically significant positive effect on Net Benefit. These results indicate that system quality, information quality, and service quality are the main determinants of perceived system benefits in this setting. The findings suggest that hospitals should prioritize technological optimization while strengthening organizational support and user readiness to maximize the success of HMIS implementation.